Rheological properties of photocurable coal-series kaolin slurry - CHEN Shu-yi; CHEN Shuang; WU Jia-min; HE Ning-hui; SHI Yu-sheng; LI Chen-hui; ZHANG Kuang; CUI Deng; WANG Yong-jun (Cailiao gongcheng, 2020)
Photocurable coal-series kaolin slurry was prepared based on photocurable resin system. The rheological properties of the slurry were characterized by a rheometer. The effect of dispersant and plasticizer addition on the rheological properties of the slurry was studied. The results show that oleic acid as a dispersant has the effect of reducing the viscosity of the slurry. When the mass fraction of oleic acid added is 1% of the kaolin powder, the viscosity of the slurry is the lowest, while the viscosity of the 40%(volume fraction) kaolin slurry is 49.56 Pa·s. Adding plasticizer PEG-300 can further reduce the viscosity of the slurry. The viscosity of the slurry decreases with the addition of plasticizer. When the plasticizer is added in the mass fraction of 20% of the photosensitive resin, the viscosity of the slurry decreases to 19.77 Pa·s, at which the requirement for good recoating is well met. The slurry with optimized rheological properties is formed in a stereolithography apparatus. After debinding and sintering, kaolin ceramics with complex shape are obtained.